2018
DOI: 10.20471/acc.2018.57.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity of Resin Based Dental Materials in Human Lymphocytes in Vitro

Abstract: SUMMARY – The aim of this in vitro study was to evaluate cytotoxicity and genotoxicity of six different dental nanocomposite materials, three conventional ones and three flowable composite resin materials, in human lymphocytes. The following materials were tested: Tetric EvoCeram, Tetric EvoFlow, Filtek Ultimate, Filtek Ultimate Flow, G-aenial and G-aenial Flo. Cytotoxicity was evaluated for two mass concentrations (0.007 g/mL and 0.013 g/mL) of each material, non-cured and cured, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…In some cases, e.g., UNI and FCR, a lower C=C conversion was not associated with higher cytotoxicity. A recent study showed that uncured composite resins may decrease cell survival by inducing early apoptosis or necrosis and genotoxicity, but the same materials had no major negative effects when tested in their polymerized condition (36). The study also showed that flowable composite resins were cytotoxic even in their cured state, reinforcing the material and formulation dependency of cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, e.g., UNI and FCR, a lower C=C conversion was not associated with higher cytotoxicity. A recent study showed that uncured composite resins may decrease cell survival by inducing early apoptosis or necrosis and genotoxicity, but the same materials had no major negative effects when tested in their polymerized condition (36). The study also showed that flowable composite resins were cytotoxic even in their cured state, reinforcing the material and formulation dependency of cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, there are various harmful effects of composites (Table 1 ) [ 11 - 17 ], although conventional composites have lower cytotoxic and genotoxic effects in comparison to uncured forms. These uncured forms of composites exhibit a high degree of cytotoxicity and genotoxicity due to their monomeric components which cause oxidative stress [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…According to studies, there are various harmful effects of composites (Table 1) [11][12][13][14][15][16][17], although conventional composites have lower cytotoxic and genotoxic effects in comparison to uncured forms. These uncured forms of composites exhibit a high degree of cytotoxicity and genotoxicity due to their monomeric components which cause oxidative stress [18]. In a study by Nascimento et al, two conventional resins, nine bulk-fill resins, and 11 different types of composite resins were tested on L929 fibroblast cell lines for cytotoxicity using the MTT (3-(4,5dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide) assay and the neutral red uptake assay.…”
Section: Cytotoxic Effectsmentioning
confidence: 99%
“…60 revealed different re-sults between the neutral red and MTT tests. Rajic et al 63 found that cured forms of composites did not show any toxic effect, whereas uncured forms exhibited a certain level of toxicity. Completely curing is not always possible due to the existence of saliva or anatomical problems in clinical conditions.…”
Section: Local Toxicitymentioning
confidence: 99%
“…Whereas, other studies did not present any evidence regarding genotoxicity of composite resins. 63,84,85 Further research about genotoxicity is required as neither of these in vivo studies evaluated the restorative materials directly on genetic material.…”
Section: Genotoxicity Studiesmentioning
confidence: 99%